2014
DOI: 10.1371/journal.pone.0089646
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ERK Pathway for Oxidant-Induced Parthanatos in Human Lymphocytes

Abstract: Reactive oxygen species (ROS) are formed by myeloid cells as a defense strategy against microorganisms. ROS however also trigger poly(ADP-ribose) polymerase 1- (PARP-1) dependent cell death (parthanatos) in adjacent lymphocytes, which has been forwarded as a mechanism of immune escape in several forms of cancer. The present study assessed the role of mitogen-activated protein kinases (MAPKs), in particular the extracellular signal-regulated kinase (ERK), in ROS-induced signal transduction leading to lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…On the one hand, ROS could lead to DNA strand breaks via causing oxidative damage of nucleic acids . On the other hand, ROS could induce ERK phosphorylation, and the phosphorylated ERK has direct regulatory effect on DNA damage‐induced PARP‐1 activation . In this study, we found that OGD induced time‐dependent overproduction of intracellular ROS, and suppression of ROS prevented markedly expressional upregulation of PARP‐1 and PAR polymer.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…On the one hand, ROS could lead to DNA strand breaks via causing oxidative damage of nucleic acids . On the other hand, ROS could induce ERK phosphorylation, and the phosphorylated ERK has direct regulatory effect on DNA damage‐induced PARP‐1 activation . In this study, we found that OGD induced time‐dependent overproduction of intracellular ROS, and suppression of ROS prevented markedly expressional upregulation of PARP‐1 and PAR polymer.…”
Section: Discussionsupporting
confidence: 51%
“…Zheng et al reported that exogenous H 2 O 2 induced expressional upregulation of PARP‐1 and obvious accumulation of PAR polymer in glioma cells . Moreover, Akhiani et al found that exogenous H 2 O 2 could trigger PARP‐1‐dependent accumulation of PAR polymer in myeloid cells . Although it is still elusive why ROS could activate PARP‐1, previous studies suggest ROS might overactivate PARP‐1 via two pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these results suggest that cell death in vanadium-exposed NK cells is secondary to non-caspase-dependent signaling. Consequently, NK cell death observed here might be a consequence of increased ERK and MEK activation (as noted in Akhiani et al 2014), since phosphorylation of BAD could not be initiated by Akt/protein kinase B (since V 2 O 5 decreased Akt expression).…”
Section: Discussionmentioning
confidence: 73%
“…7 Reactive oxygen species (ROS)-induced NK cell dysfunction is considered one of the mechanisms of 'immune escape' at sites of solid tumour progression. 8 Furthermore, tumour-associated monocytes/macrophages 9 or myeloid cells 10 suppress NK cells in an oxidant-dependent manner. Oxidative stress is also responsible for the suppression of NK cell functions in non-malignant pathological conditions, such as uraemia 11,12 or atherosclerosis.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%